Penerapan Metode PBL untuk Meningkatkan Kemampuan Berpikir Kritis Fase E di Smak Seminari Mario John Boen Pangkalpinang - Maria Margaritha de Lellis Priyati Dua Ploe; Hartutik Hartutik; Sugiyana Sugiyana (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
At SMAK Seminari Mario John Boen, students' critical reasoning and cognitive abilities were found to be underdeveloped due to conventional, lecture-based teaching methods that lacked creativity and student involvement. This study aimed to enhance students' critical reasoning through the implementation of the Problem-Based Learning (PBL) method, which promotes creative and student-centered learning. Conducted as Classroom Action Research, the study involved 25 students in class X, phase E, and was carried out over two cycles, each consisting of four stages: planning, implementation, evaluation, and reflection. The PBL approach was applied to the Holy Trinity subject matter, with a focus on the critical reasoning dimension of the Pancasila Student Profile (P3), targeting the development of both cognitive and affective domains. Data were analyzed descriptively. The findings revealed a significant improvement in the affective aspect of critical reasoning, increasing from 56.67 in cycle 1 to 69.33 in cycle 2. Similarly, cognitive scores rose from 60.12 to 75.72. Achievement levels showed that 28% of students reached the Advanced stage, 48% the Proficient stage, 16% the Adequate stage, and 8% remained Undeveloped. Reflection results suggest the need for continued support in the affective domain. Overall, the research concludes that the Problem-Based Learning method, when aligned with the critical reasoning component of Pancasila Student Profile, effectively improves student learning outcomes both cognitively and affectively.